A comprehensive overview of drug delivery systems for tumor treatment - Alhabib, Nasser Ali; Alehaidib, Soliman Mohammed; Almansour, Mohammed Ahmed; Aldosary, Mubarak Saad; Almegbel, Maysam Taysir; Alzahrani, Ahlam Mohammed (International journal of health sciences, 2021)
Background: With 19.3 million new cancer cases and 10 million related deaths globally in 2020, there is an urgent need for effective cancer treatments. Traditional modalities such as surgery, radiotherapy, and chemotherapy have limitations, particularly for aggressive and metastatic cancers, leading to high recurrence rates and poor outcomes. The development of advanced drug delivery systems (DDS) is emerging as a promising strategy to enhance treatment efficacy and reduce side effects. Aim: This review aims to provide a comprehensive overview of the various drug delivery systems employed in tumor treatment, highlighting their preparation, characteristics, applications, and clinical potential. Methods: The review covers a range of drug delivery carriers including nonmetallic nanoparticles, metal nanoparticles, albumin, ferritin, liposomes, exosomes, and dendrimers. The focus is on their design, functionalization, and effectiveness in delivering antitumor drugs. Additionally, it discusses the integration of various anticancer agents with these delivery systems and their impact on treatment efficacy. Results: Recent advancements in DDS have shown significant improvements in drug targeting and delivery. For instance, second-generation nanomedicines with active targeting mechanisms have demonstrated enhanced specificity and reduced systemic toxicity. Notable developments include pegylated liposomal doxorubicin, ferritin-based drug carriers, and exosome-sheathed nanoparticles.